A Study on the evaluation and development of welfare policy for soldiers using AHP - JANG, Yuji (KDI School, 2022)
The Republic of Korea is adopting a conscription system due to financial reasons, added with the reality of Korea being a divided country that must actively respond to North Korea's direct provocations and threats caused by their uncertain, volatile system. This implies that since the Korean military is operated on the premise of a conscription system based on national defense obligations, active-duty soldiers are forced to continuously adapt it environments rapidly changed by external forces. In the process, some experience maladjustment, or become either serious perpetrators or victims of toxic culture existing in barracks such as bullying, suicide, violence and unjust behavior. Accordingly, the Ministry of National Defense promoted several military welfare policies with the basic agenda to fundamentally resolve the repeating problems in the barracks. However, despite the steady efforts of the Ministry of National Defense, the level of soldiers' feelings for improving treatment is low because the Korean military has led the policy from the supplier's point of view without trying to properly grasp the welfare needs of soldiers based on professional methods. Therefore, this study attempted to recognize welfare needs from the perspective of beneficiaries by examining what welfare policies are mainly preferred by active-duty soldiers using AHP research techniques. As a result of the AHP survey, the most preferred policy for active-duty soldiers was to expand the usage of smartphones (0.377), followed by a policy (0.145) that supports soldiers with approximately 100,000 won for self-development activities. On the other hand, their least preferred policy was the policy to support haircuts expenditures for soldiers (0.007). This is because there was no opportunity to use private salons amid continuous restrictions on going out or vacation due to COVID-19. In other words, welfare programs that have no utility value for soldiers only wastes the budget, and this study emphasizes that for the efficient execution of a limited budget, the survey of beneficiaries' needs must precede the establishment of welfare plans. Furthermore, this study proposes two alternatives for more efficient execution of the welfare budget. The first is to increase the autonomy of active-duty soldiers' welfare choices. By providing cashable welfare, not in kind, the system needs to be improved so that active- duty soldiers can each choose more necessary welfare. The second is to prepare various contents that can use a smartphone. Simply extending smartphone usage time should be avoided as it can be a risk to the military's original purpose of national defense. However, for example, contracts with companies that provide e-book rental services can provide welfare so that soldiers can experience various cultural lives with smartphones during off-work hours. Preparing various contents using smartphones can be an alternative to more efficiently utilizing the welfare budget in that it can provide non-exclusion and non-economical welfare benefits.
Thesis(Master) -- KDI School: Master of Public Policy, 2022
Keywords: Public welfare--Korea (South); Soldiers--Welfare state